AN ISOCOUMARIN DERIVATIVE FROM PAEPALANTHUS BROMELIOIDES - Tomita, K.; Vilegas, Wagner [UNESP] (Munksgaard Int Publ Ltd, 1994)
The structure of 5,7,9,10-tetramethoxy-3-methyl-1 H-naphtho[2,3-c]pyran-1-one, C18H18O6, a derivative of a natural isocoumarin isolated from Paepalanthus bromelioides, was determined by X-ray analysis, which unequivocally confirmed the previously assigned structure. Small deviations from the standard angles, resulting from steric hindrance between the methoxyl and carbonyl groups, were observed.